Beauty and the beast [compact disc] - Menken, Alan; Ashman, Howard; Benson, Robby; Corti, Jesse; Lansbury, Angela, 1925-2022; O'Hara, Paige; Orbach, Jerry; Stiers, David Ogden; White, Richard, 1953-; Friedman, David, 1950-; Dion, Céline; Bryson, Peabo; et al. (Walt Disney Records, 2010)
A classic album is reissued to celebrate the release of the Diamond Edition of Disney's Beauty and the Beast on 10/05/10. Includes a new recording of the song Beauty and the Beast by Jordin Sparks.